2018
DOI: 10.1002/ijgo.12471
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the desire for companionship during labor in a Nigerian community

Abstract: Most couples had negative attitudes toward companionship during labor. Intensive education programs and restructuring of facilities could enable Nigerian labor wards to improve the delivery experience for both parturients and their male partners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
(57 reference statements)
0
3
2
Order By: Relevance
“…In contrast, this rate is higher than was reported in a study conducted in rural central Ghana which showed that 58% of mothers utilize companionship during delivery [26]. The finding of this study is lower than the study reported in Nigeria which showed that only 22.1% of mothers companionship during delivery [27].…”
Section: Discussioncontrasting
confidence: 87%
“…In contrast, this rate is higher than was reported in a study conducted in rural central Ghana which showed that 58% of mothers utilize companionship during delivery [26]. The finding of this study is lower than the study reported in Nigeria which showed that only 22.1% of mothers companionship during delivery [27].…”
Section: Discussioncontrasting
confidence: 87%
“…There is evidence that shows women who live in the marginalized area of Ethiopia with limited educational level are highly experiencing traditional birth attendants, and even they need to make them as companion at the health facility ( 32 , 33 ). The finding of this study also higher than study conducted in Arba Minch Ethiopia (43.7%) ( 12 ), Kenya (37%) ( 9 ), Nigeria (22.1%) ( 34 ), and Tanzania (44.7%) ( 11 ). The possible explanation for higher magnitude in this study compared to the study conducted at Arba Minch Ethiopia might be due to the variation in the study population.…”
Section: Discussioncontrasting
confidence: 72%
“…However, in other countries, views may be different. For example, in Nigeria and Russia women preferred their partner not to be present during birth (Adeyemi et al 2018;Baktha and Lee 2010;Oboro et al 2011). Thus, the issue of lay companionship's support during childbirth may be influenced by the context of specific countries and cultures.…”
Section: Introductionmentioning
confidence: 99%